The Ethical Business : Challenges and controversies - Mellahi, Kamel; Wood, Geoffrey E. (Geoffrey Edward), 1945- (Basingstoke : Palgrave Macmillan, 2003)
In this text, the authors will provide an up-to-date coverage of key issues and perspectives in business ethics from a critical perspective.
Includes bibliographical references (p. 148-160) and index.
Keywords: Business ethics; Society